Overexpression of the Novel Arabidopsis Gene At5g02890 Alters Inflorescence Stem Wax Composition and Affects Phytohormone Homeostasis - Xu, Liping; Zeisler, Viktoria; Schreiber, Lukas; Gao, Jie; Hu, Kaining; Wen, Jing; Yi, Bin; Shen, Jinxiong; Ma, Chaozhi; Tu, Jinxing; Fu, Tingdong (Frontiers in Plant Science, 2017)
The cuticle is composed of cutin and cuticular wax. It covers the surfaces of land plants and protects them against environmental damage. At5g02890 encodes a novel protein in Arabidopsis thaliana. In the current study, protein sequence analysis showed that At5g02890 is highly conserved in the Brassicaceae. Arabidopsis lines overexpressing At5g02890 (OE-At5g02890 lines) and an At5g02890 orthologous gene from Brassica napus (OE-Bn1 lines) exhibited glossy stems. Chemical analysis revealed that overexpression of At5g02890 caused significant reductions in the levels of wax components longer than 28 carbons (C28) in inflorescence stems, whereas the levels of wax molecules of chain length C28 or shorter were significantly increased. Transcriptome analysis indicated that nine of 11 cuticular wax synthesis-related genes with different expression levels in OE-At5g02890 plants are involved in very-long-chain fatty acid (VLCFA) elongation. At5g02890 is localized to the endoplasmic reticulum (ER), which is consistent with its function in cuticular wax biosynthesis. These results demonstrate that the overexpression of At5g02890 alters cuticular wax composition by partially blocking VLCFA elongation of C28 and higher. In addition, detailed analysis of differentially expressed genes associated with plant hormones and endogenous phytohormone levels in wild-type and OE-At5g02890 plants indicated that abscisic acid (ABA), jasmonic acid (JA), and jasmonoyl-isoleucine (JA-Ile) biosynthesis, as well as polar auxin transport, were also affected by overexpression of At5g02890. Taken together, these findings indicate that overexpression of At5g02890 affects both cuticular wax biosynthesis and phytohormone homeostasis in Arabidopsis.